2016
DOI: 10.1016/j.wear.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate microstructure and surface finish on cracking and delamination response of TiN-coated cemented carbides

Abstract: The cracking and delamination of TiN-coated hardmetals (WC-Co cemented carbides) when subjected to Brale indentation were studied. Experimental variables were substrate microstructure related to low (6 wt% Co) and medium (13 wt% Co) binder content, and surface finishes associated with grinding and polishing stages before film deposition. Brale indentation tests were conducted on both coated and uncoated hardmetals. Emphasis has been placed on assessing substrate microstructure and subsurface finish effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…In the case of the cBN substrate, d is clearly present even for the smaller loads. As the load increases, more spa coating is observed, similar to previous research on similar materials[34,45,46…”
supporting
confidence: 90%
“…In the case of the cBN substrate, d is clearly present even for the smaller loads. As the load increases, more spa coating is observed, similar to previous research on similar materials[34,45,46…”
supporting
confidence: 90%
“…Accordingly, strength is effectively defined by the combined influence of the depth and magnitude of the residual stresses induced within the subsurface, geometry of the induced cracks, and the synergic interaction of these features with microstructure and processing defects [22][23][24][25][26][27]. Studies reporting the combined influence of grinding and coating on induced changes in residual stress state, adhesion strength, and contact damage resistance exist [20,[28][29][30][31]. However, information of how grinding and coating collectively affect the fracture resistance is limited for these materials [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications, authors have shown that grinding induced microcracks exist down to a depth of about 2 μm, and microcracking followed two different microstructural paths: either WC/Co interfaces or transgranular within the carbide phase, whereas the former being more predominant than the latter for the same material and grinding conditions used in the current study [15,18,19].…”
Section: Correlation Of the Metallurgical Alterations In The Metallicmentioning
confidence: 59%
“…However, similar to other hard and brittle materials [8][9][10], as a result of the abrasive operation, surface integrity of hardmetals is altered at both surface and subsurface levels, particularly in terms of microcracks, residual stresses, and metallurgical alterations within the metallic binder. Thus, mechanical and tribological performance of corresponding tools and components are also affected [6,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%